Cup, Cup, Jangan Nangis! Language Socialization Study of How Parents Respond to Their Children Cry - Kurniawati, Wira; Putri, Clorinda Zakiyya; Nugroho, Amanda Aurelia (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Burdelski & Cook (2012) and Santrock (2011) theorized that parents socialize with their children through actions and speech, even when responding to the cries of their children. This paper intends to investigate the actions and speech of parents when responding to their cries. This paper also aims to understand how parents socialize with their children in those activities. The researcher conducted this qualitative research by distributing questionnaires via Google Forms. WhatsApp groups and Twitter are the media the researcher chose to distribute the form. After receiving 98 answers, the researcher interviewed 24 families—picking two for further observations. The result shows that parents convey their responses through one, two, or more speech acts that include assertive in the forms of an affirmation; directives in the forms of prohibition, advice, encouragement, asking (general question, assurance, investigation, rhetorical); expressive in the forms of an expression of getting surprised, teasing, showing caring expression, calming down, and blaming; and commissive in the forms of promising. Meanwhile, there are various socialization functions contained in these speech acts, such as affective socialization (in the form of caring or concern and reassurance), self-knowledge socialization (in the form of self-confidence, prudence), socialization of gender identity (maturity and gender), religiosity, shame, causal logic or the consequences, and even logical fallacy for blaming something that has nothing to do with the cause of the child falling.